Nanoparticle-aided detection of colorectal cancer-associated glycoconjugates of extracellular vesicles in human serum - Vinod Rufus; Mahran Randa; Routila Erica; Leivo Janne; Pettersson Kim; Gidwani Kamlesh (MDPI, 2022)
Extracellular vesicles (EVs) are found in all biological fluids, providing potential for the identification of disease biomarkers such as colorectal cancer (CRC). EVs are heavily glycosylated with specific glycoconjugates such as tetraspanins, integrins, and mucins, reflecting the characteristics of the original cell offering valuable targets for detection of CRC. We report here on europium-nanoparticle (EuNP)-based assay to detect and characterize different surface glycoconjugates of EVs without extensive purification steps from five different CRC and the HEK 293 cell lines. The promising EVs candidates from cell culture were clinically evaluated on small panel of serum samples including early-stage (n = 11) and late-stage (n = 11) CRC patients, benign condition (n = 11), and healthy control (n = 10). The majority of CRC cell lines expressed tetraspanin sub-population and glycovariants of integrins and conventional tumor markers. The subpopulation of CD151 having CD63 expression (CD151CD63) was significantly (p = 0.001) elevated in early-stage CRC (8 out of 11) without detecting any benign and late-stage samples, while conventional CEA detected mostly late-stage CRC (p = 0.045) and with only four early-stage cases. The other glycovariant assays such as CEACon-A, CA125WGA, CA 19.9Ma696, and CA 19.9Con-A further provided some complementation to the CD151CD63 assay. These results indicate the potential application of CD151CD63 assay for early detection of CRC patients in human serum.